Pembangunan akhlak dalam kalangan pelajar institusi pengajian tinggi awam di Malaysia menerusi penerapan kemahiran insaniah - Rashidi, Abbas (2013)
This study was conducted to find out the akhlak development among students of Higher Learning Institutions in Malaysia through the application of Soft Skills. The samples are the undergraduate students who are in the sixth semester of their studying at the MTUN (Malaysian Technical University Network) consist of the Universiti Malaysia Pahang (UIVIP), the Technical University of Màlàysia Melaka (UTeM), the Universiti Tun Hussein Onn (UTHM) and the Universiti Malaysia Penis (UniMAP). The number of samples/respondents is 480 people and distributed to the respondents using cluster sampling techniques. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 19.0 for the mean, standard deviation and Pearson Correlation. The result showed that there is a moderate but significant relationship between possessing akhlak with the communication skills ability, professional ethics and moral, teamwork, entrepreneurship and continuous learning and information management. Meanwhile, there is a weak relationship between critical thinking and problem solving with akhlak. However, there is strong relationship between akhlak with leadership skills. Moreover, the findings showed a weak relationship between akhlak with the teaching and learning methodology. However, data shows high ability in terms of mastery of soft skills, ethical and moral skills, teamwork, entrepreneurship, critical thinking and problem solving, leadership, continuous learning and information management. Only communication skills show moderate score In conclusion, this study shows that there is a significant correlation between akhlak and mastery of soft skills. Proper attention should be given to this realm inorder to further enhance the students' potential as well as to improve the performance of university.